2013
DOI: 10.1002/hyp.9752
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of varied complexity models simulating recharge at the field scale

Abstract: Numerical models are frequently used for the regional quantification of groundwater recharge. However there is a wide range of potential models available that represent the land surface with varying degrees of complexity, but which are rarely tested against observations at the field scale. We compared four models that simulate potential recharge at four intensively monitored sites with different vegetation and soil types in two adjacent catchments. These models were: Penman–Grindley, UN Food and Agricultural O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 52 publications
1
22
0
Order By: Relevance
“…This is why all simplified groundwater recharge models perform well for historical years with average temperature ranges and precipitation amounts but performance is different for extremes. These observations are in line with the study of Sorensen et al (2014). They show a generally good agreement between simulated and observed soil moisture content for four soil-water-balance models but significant differences occur under extreme periods and in the seasonal patterns.…”
Section: Relation Between Model Simplification and Model Performancesupporting
confidence: 90%
“…This is why all simplified groundwater recharge models perform well for historical years with average temperature ranges and precipitation amounts but performance is different for extremes. These observations are in line with the study of Sorensen et al (2014). They show a generally good agreement between simulated and observed soil moisture content for four soil-water-balance models but significant differences occur under extreme periods and in the seasonal patterns.…”
Section: Relation Between Model Simplification and Model Performancesupporting
confidence: 90%
“…Hence, the choice of a model needs to be based on the objective of a project and availability of datasets. As pointed out by Alley (1984), Gee and Hillel (1988) and Sorensen et al (2014), models that treat soil layers as several reservoirs are likely to produce differing recharge estimates, because of different approaches used for water budget partitioning. Sorensen et al (2014) demonstrated that soil moisture data alone are unable to constrain groundwater recharge in four commonly used water balance models, consistent with our study.…”
Section: Comparison To Other Water Balance Modelsmentioning
confidence: 99%
“…Even so, to satisfy the water balance, an explicit representation of the soil zone for model nodes that are not ice or snow-covered was included using the method developed by Griffiths et al (2006) which has been successfully applied to temperate regions in the past (Mackay et al, 2014;Sorensen et al, 2014) and is based on the well 30 established UN Food and Agricultural Organisation soil water balance method (Allen et al, 1998 defines the maximum volume of water available to plants for evapotranspiration after the soil has drained to its field capacity and can be defined from lookup tables with basic information on vegetation and soil information (Allen et al, 1998). This was parametrised using the 'Talus' soil class and 'semi-vegetated' land surface class giving an average T AW value of 7 mm.…”
Section: A1 Soil Infiltration and Evapotranspirationmentioning
confidence: 99%